Effects of fennel (Foeniculum vulgare) seed powder addition during early lactation on performance, milk fatty acid profile, and rumen fermentation parameters of Holstein cows - Moosavi-Zadeh, Erfaneh; Rahimi, Amin; Rafiee, Hassan; Saberipour, Hamidreza; Bahadoran, Ramin (Frontiers in Animal Science, 2023)
Aromatic and herbal plants usage as feed additives have become a new tendency in dairy cows’ nutrition to enhance animal performance. This experiment was performed to study the effects of supplementing fennel seed powder (FSP) to diets during early lactation on performance, milk fatty acid (FA) profile, and rumen fermentation of Holstein dairy cows. Twenty-four primiparous Holstein dairy cows (10 ± 3 d in milk, 30 ± 2.1 Kg of milk/d, 610 ± 31 Kg body weight; mean ± SE) were balanced for actual milk yield and calving date (n = 8 per treatment) in a complete randomized design. Animals were allocated randomly to diets containing 0 g/d (0FSP), 25 g/d (25FSP), or 50 g/d (50FSP) FSP, individually top-dressed over the total mixed ration. The experimental period was 45 d consisting of the first 15 d for adaptation and the final 30 d for data collection and sampling. Dry matter intake responded quadratically to FSP feeding, and cows fed 25FP treatment had greater DMI than 0FSP treatment. The average ruminal pH value decreased linearly as FSP increased in diets. Ruminal valerate and isovalerate proportion increased linearly as FSP inclusion in diets increased, while acetate proportion decreased and acetate:propionate ratio tended to decrease linearly. Increasing FSP in diets linearly increased serum glucose, globulin, and total protein concentrations. Milk yield increased linearly as FSP inclusion in diets increased, whereas milk composition was unaffected. Increasing FSP in diets linearly increased de novo and mixed FA and decreased preformed FA in milk. Dietary treatments did not affect saturated FA, whereas unsaturated FA, mono and poly unsaturated FA linearly decreased with increasing FSP inclusion in diets. Moreover, the content of C18:0 tended to decrease, and C18:1 cis-9 decreased linearly as FSP inclusion increased. Also, increasing the FSP level in diets decreased linearly non-esterified fatty acids and acetone concentrations in the milk. It could be concluded that FSP addition at 50 g/d could enhance performance of early lactating cows.